Light scattering by ice crystals of cirrus clouds: comparison of the physical optics methods - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The physical optics approximations are derived from the Maxwell equations. The scattered field equations by Kirchhoff, Stratton-Chu, Kottler and Franz are compared and discussed. It is shown that in the case of faceted particles, these equations reduce to a sum of the diffraction integrals, where every diffraction integral is associated with one plane–parallel optical beam leaving a particle facet. In the far zone, these diffraction integrals correspond to the Fraunhofer diffraction patterns. The paper discusses the E-, M- and (E, M)-diffraction theories as applied to ice crystals of cirrus clouds. The comparison to the exact solution obtained by the discontinuous Galerkin time domain method shows that the Kirchhoff diffraction theory is preferable.
Keywords: tet_topic_scattering